SISTEM INFORMASI GEOGRAFIS PENGEMBANGAN POTENSI INDUSTRI KECIL DAN MENENGAH KABUPATEN KUNINGAN BERBASIS WEB - Yati Nurhayati; Riyan Febriyana (NUANSA INFORMATIKA, 2011)
Kuningan Regency has the potential sources, both the potencies of small and medium industries,agriculture, and livestock. As effort to develop the potential region, technological approach in obtaining the information is still lack. By using technology the potential information is expected to be accepted optimally by the society, and potentially regional development can be planned well. This condition can overcome by the Geographic Information System (GIS) that can provide the data attributes of an object map and spatial data. The role of GIS in the development potential can be used as a tool taking action against a potential area for further development. GIS is presented with a web-based on this design. It can also be used as a tool to provide information to the public. Keyword :potential, information,technology, GIS, map